Evaluation of the Impact of Genetically Modified Cotton After 20 Years of Cultivation in Mexico - Rocha-Munive, Martha G.; Soberón, Mario; Castañeda, Saúl; Niaves, Esteban; Scheinvar, Enrique; Eguiarte, Luis E.; Mota-Sánchez, David; Rosales-Robles, Enrique; Nava-Camberos, Urbano; Martínez-Carrillo, José L.; Blanco, Carlos A.; Bravo, Alejandra; et al. (Frontiers in Bioengineering and Biotechnology, 2018)
For more than twenty years cotton has been the most widely sown genetically modified (GM) crop in Mexico. Its cultivation has fulfilled the regulatory requirements and has gone through different regulatory stages. During the last 20 years, both research-institutions and biotech-companies have generated scientific and technical information regarding GM cotton cultivation. In this work, we collected data in order to analyze the environmental and agronomic effects of the use of GM cotton in Mexico. In 1996, the introduction of Bt cotton made it possible to reactivate the cultivation of this crop, which in previous years was greatly reduced due to pest problems, production costs and environmental concerns. Bt cotton is a widely accepted tool for cotton producers and has proven to be efficient for the control of lepidopteran pests. The economic benefits of its use are variable, and depend on factors such as the international prices and the costs associated with its inputs. So far, the insecticide resistance management used to prevent development of insect resistance to GM cotton has been successful, and there are no reports of insect resistance development to Bt-cotton in Mexico. In addition, no effects have been observed on non-target organisms. For herbicide tolerant cotton, the prevention of herbicide resistance has been successful and, unlike other countries, the onset of resistance weeds is still slow, apparently due to cultural practices and rotation of different herbicides. Environmental benefits have been achieved with a reduction in chemical insecticide applications and subsequent decrease in primary pest populations, so that the inclusion of other technologies –e.g., use of non-Bt cotton- can be explored. Nevertheless, control measures need to be implemented during transport of the bolls and after the fiber less seeds leave the gins, to prevent volunteer dispersal and subsequent gene flow to wild relatives distributed outside the cotton growing areas. It is still necessary to implement national research programs, so that biotechnology and plant breeding advances can be used in the development of cotton varieties adapted to conditions of the country and to control insect pests of national and regional importance.